Exploring the role of teacher empathy in student mental health outcomes: a comparative SEM approach to understanding the complexities of emotional support in educational settings - Ampofo, Joshua; Bentum-Micah, Geoffrey; Xusheng, Qian; Sun, Binghai; Mensah Asumang, Rita (Frontiers in Psychology, 2025)
IntroductionThis study investigates the role of teacher empathy in influencing student mental health outcomes through a comparative Structural Equation Modeling (SEM) approach. Given the rising prevalence of mental health challenges among students, understanding the impact of empathetic teacher-student relationships is crucial.MethodsUtilizing a sample of 300 students from diverse educational settings, the research examines how teacher empathy affects student engagement and mental health. The study employs SEM to analyze the relationships between perceived teacher empathy, student engagement, and mental health outcomes.ResultsFindings reveal that higher levels of perceived teacher empathy correlate with reduced stress, anxiety, and depression while enhancing student engagement in learning activities. Furthermore, student engagement mediates the relationship between teacher empathy and mental health outcomes.DiscussionThe results underscore the necessity of fostering empathetic relationships within educational contexts to promote student resilience and well-being. Implications for teacher training programs and academic practices are discussed, emphasizing the importance of empathy in creating supportive learning environments that enhance student mental health and engagement.